Exploring the Notion of the Europeanization of Public Spheres and Civil Society in Fostering a Culture of Dialogue Through the Concept of “Proper Distance” - Wessels, Bridgette (Sociologija. Mintis ir veiksmas, 2015)
An ideal-type public sphere provides space for public debate regarding what makes for a ‘good society’, and for consideration of the issues involved in the development and sustainability of such a society. In general terms these debates are historically situated and nationally understood. Current developments in the process of fostering some development in the Europeanization of public spheres raise specific questions, such as: what are the obstacles for creating European public spheres that are inclusive for different groups in Europe? What is the role of the media in constructing civic cultures in Europe? To gain an understanding of the dynamics of the role of the media in relation to civil society involves understanding the ways in which the media and participation are culturally embedded and understood in late modernity and in the expansion of the European Union. Within Europe, cultural distinctiveness emerges through differences in ways of life and their respective institutional expression as well as personal and group identity formations. Dewey’s (1939) claim that society is realised through communication allows one to explore the question of cultural expression and dialogue in tracing the articulation of cultures within a changing Europe. The framework of analysis is that of ‘communication spaces’ of digital media and mass media in relation to the dynamics of participation. The paper draws on comparative European research of migrant and minority communities within Europe as well as more settled communities in Europe. The case studies show how mass media and new media are differentially appropriated within various contexts of use. The concept of ‘proper distance’ (Silverstone 2007) is used to explore these developments and to analyse the role of the media more generally in a changing Europe. Proper distance includes issues such as hospitality, responsibility and trust in the mediation of public and everyday life. It critically assesses the capacity of current mainstream mediato engender dialogue between the peoples of Europe with a focus on fostering respect and understanding in the creation of inclusive public spheres in the context and contradictions of Europeanization.